Histological Evidence for the Enteric Nervous System and the Choroid Plexus as Alternative Routes of Neuroinvasion by SARS-CoV2 - Felix Deffner; Melanie Scharr; Stefanie Klingenstein; Moritz Klingenstein; Alfio Milazzo; Simon Scherer; Andreas Wagner; Bernhard Hirt; Andreas F. Mack; Peter H. Neckel (Frontiers Media S.A., 2020)
Evidence is mounting that the novel corona virus SARS-CoV2 inflicts neurological symptoms in a subgroup of COVID-19 patients. While plenty of theories on the route of neuroinvasion have been proposed, little histological evidence has been presented supporting any of these hypotheses. Therefore, we carried out immunostainings for ACE2 and TMPRSS2, two proteinases crucial for the entry of SARS-CoV2 into host cells, in the human enteric nervous system (ENS), as well as in the choroid plexus of the lateral ventricles. Both of these sites are important, yet often neglected entry gates to the nervous system. We found that ACE2 and TMPRSS2 are expressed by enteric neurons and glial cells of the small and large intestine, as well as choroid plexus epithelial cells, indicating that these cells meet the molecular requirements for viral entry. Together, our results are fundamental histological evidence substantiating current theories of neuroinvasion by SARS-CoV2.